Organic Electrosynthesis: A Promising Green Tool in Solving Key Steps for the Total Synthesis of Complex Natural Products - Bandyopadhyay, Ayan; Sarkar, Rajib (Current Green Chemistry, 2024)
Electro-organic synthesis, an atom-efficient, sustainable, mild process, permits an ecofriendly and elegant green path to synthesize structurally complex, still valuable molecules, avoiding the use of conventional harsh oxidizing and reducing agents and long-route reaction protocols. Being one of the oldest forms of reaction setups in a laboratory, it deals with fundamental redox chemistry through the direct application of electrical potential. Here flow of electrons acts as an oxidizing agent at the anode at the same time reducing agent at the cathode, depending upon the requirement of the reaction. Simultaneously, it minimizes the generation of reagent waste during the reaction. However, electrifying organic synthesis plays more than preventing the waste footprint. This technology provides an alternative roadmap through nonclassical bond disconnections to access desired target molecules by cutting down a number of steps with the formation of apparently looking difficult bonds with excellent regio-, chemo-and stereoselectivity. Hence, it emerges as an alternative and attractive technique for the contemporary synthetic communities. Consequently, in recent years, multiple milestones have been achieved in the electro-organic synthesis of fascinating natural products through oxidative C-C bond formation, C-H/N-H functionalization, very rare oxidative N-N dimerization, RCDA dimerization, etc. Thus, synthesis of extremely complex natural products through finding new electro-synthetic route as a key methodology have become one of the alluring synthetic targets to synthetic chemists because of their versatile utilities in medicine, agriculture, food, and cosmetic industry. This review presents advances in electrochemistry in the total synthesis of 20 complex natural products reported since 2013. Enabling synthetic steps are analyzed alongside innate advantages as well as future prospects are speculated.
Keywords: organic synthesis